Gout treatment-helpful treatment options - Devaraj, Navin Kumar (2019)
Gout is a relatively common condition affecting those as young as those in their 20’s. There are many risk factors. This case report looks at a 40 years old man who had many acute gout attacks and what treatment options were helpful for him.